Kit Solar Sel/Panel Surya Sebagai Media Pembelajaran pada Materi Efek Fotolistrik - Yusra Defawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The aim is to motivate students in learning the photoelectric effect, the method used in this study is inquiry learning with the result that students can more easily understand the working principle of solar cells / solar panels so that learning is more edible and students understand it more easily. For students learning with this solar panel kit can add knowledge horizons and apply them, and give birth to new innovations. For teachers to be able to create a fun and meaningful learning atmosphere by further increasing creativity and innovation in learning. Schools as a means for teachers and students to interact can support and support, so that the learning process produces output that is valuable and characterized, and creative. Keywords: Solar cell / solar panel kit, learning media, microscopy, NPN transitor